The effect of the common bond and membership expansion on credit union risk - W. Scott Frame; Gordon V. Karels; Christine McClatchey (Federal Reserve Bank of Atlanta, 2001)
This paper examines differences in institutional risk profiles based on credit union membership type and membership expansion via "select employee groups," or SEGs, which are now expressly allowed by the Credit Union Membership Access Act of 1998. A cross-sectional statistical model is specified that examines risk variation relative to the type of common bond and the breadth of the credit union's membership. In findings that are consistent with earlier research, the authors document that occupationally based credit unions have a unique risk profile relative to other common bonds. This profile includes a greater exposure to concentration risk, which is hedged by holding greater proportions of capital. ; The authors also examine the subsample of Single-Bond occupational credit unions and those Multi-Bond credit unions with primarily occupational group members. They find that the presence of SEGs is negatively related to capital ratios and positively related to loan-to-share ratios relative to the Single-Bond occupational credit unions. The use of survey data documenting the number of SEGs confirms that, as more SEGs are added, credit unions tend to increase their loan-to-share ratios and decrease their capital ratios. However, the number of SEGs and the proportion of loan delinquencies are found to be positively related, suggesting that the informational advantages associated with the common bond become diluted as new groups are added. Overall, the authors conclude that there are material benefits of credit union membership diversification and that these benefits derive from expanded investment opportunities and reduced concentration risk.
Keywords: 330; Credit unions; Risk